Reporting of angiographic studies in patients diagnosed with a cerebral arteriovenous malformation: a systematic review [version 3; peer review: 1 approved, 2 approved with reservations] - Hiren Patel; Mueez Waqar; Adrian Parry-Jones; Suparna Das; Paul Kasher (F1000Research, 2024)
A cerebral arteriovenous malformation (cAVM) is an abnormal tangle of cerebral blood vessels. The consensus document by the Joint Writing Group (JWG) highlighted which cAVM features should be recorded. Subsequent publications have reported cAVM angioarchitecture, but it is unknown if all followed the JWG recommendations. The aim of this systematic review was to describe use of the JWG guidelines. A database search, using the PRISMA checklist, was performed. We describe the proportion of publications that used JWG reporting standards, which standards were used, whether the definitions used differed from the JWG, or if any additional angiographic features were reported. Out of 4306 articles identified, 105 were selected, and a further 114 from other sources. Thirty-three studies (33/219; 15%) specifically referred to using JWG standards. Since the JWG publication, few studies have used their standards to report cAVMs. This implies that the angioarchitecture of cAVMs are not routinely fully described.